Development of a GFP‐based biosensor for detecting the bioavailability and biodegradation of polychlorinated biphenyls (PCBs) - Liu, Xuemei; Germaine, Kieran J.; Ryan, David; Dowling, David N. (Journal of Environmental Engineering and Landscape Management, 2007)
Two whole‐cell biosensors were constructed to detect the in situ biodegradation of polychlorinated biphenyl by chromosomal insertion of a mini‐Tn5‐Kmr‐Pm::gfp[mut3]‐T0‐T1 construct into P. fluorescens. In vitro tests showed that the expression of the Pm promoter depended on the growth phase of the biosensors and the concentration of chemical inducers; chlorinated benzoic acid derivatives. A linear relationship between the fluorescent intensity and the log10 concentration of the inducer was observed. One biosensor (F113L::1180gfp) had the ability to degrade PCBs to relevant chlorobenzoic acid derivatives and to induce expression of Gfp. The second biosensor (F113gfp), which cannot degrade PCBs, shows fluorescence after induction by chloro‐benzoic acid derivatives. By using these two biosensors, PCB degradation could be detected in vitro and in soil.Gfp pagrindo biosensorių tobulinimas polichlorintų bifenilų (PCBs) biotinkamumui ir biodegradacijai nustatytiSantrauka. Sukonstruoti du ląsteliniai bioindikatoriai polichlorintų bifenilų in situ biodegradacijai nustatyti chromosominiu konstrukto mini-Tn5-KmF -Pm::gfp[mut3]-T0 -T1 įterpimo į P. fluorescens būdu. Bandymai dirbtinėmis sąlygomis parodė, kad Pm aktyviklio išraiška priklauso nuo bioindikatoriaus augimo fazės ir cheminių indikatorių koncentracijos, taip pat nuo chlorintų benzenkarboksirūgščių derinių. Nustatyta tiesinė priklausomybė tarp fluorescentų intensyvumo ir indikatorių log10 koncentracijos. Vienas iš bioindikatorių (F113L::1180gfp) galėjo degraduoti PCBs iki tinkamų chlorobenzenkarboksirūgščių derinių ir indukuoti Gfp išraišką. Antrasis bioindikatorius (F113gfp), kuris negali degraduoti PCBs, parodo fluorescentiškumą įvykus indukcijai pagal chloro-benzenkarboksirūgščių derinius. Naudojant šiuos du bioindikatorius, PCB degradacija gali būti nustatyta tiek dirbtinėmis sąlygomis, tiek dirvožemyje.Reikšminiai žodžiai: bioindikatoriai, Pseudomonas fluorescens F113, PCBs, rizosfera, šaknų kolonizacija.Совершенствование биосенсоров основы gfp для определения биосоответствия и биодеградации полихлорированных бифенилов (PCBs)Резюме. Сконструированы два клеточных биоиндикатора для выявления на участке биодеградации полихлорированных бифенилов путем хромосомного введения мини-Tn5-Kmr-Pm::gfp[mut3]-T0-T1 в P. fluorescen. Испытания в искусственных условиях показали, что выражение активатора Pm зависит от фазы роста биоиндикатора и концентрации химических индикаторов, а также от сочетаний хлорированных бензойных кислот. Наблюдалась линейная зависимость между интенсивностью флуоресцентов и концентрации log10 индикаторов. Один из индикаторов (F113L::1180gfp) мог способствовать деградации PCBs в сочетания соответствующих хлор-бензойных кислот и индуцировать выражение Gfp. Другой биоиндикатор (F113gfp), который не может способствовать деградации PCBs, показал флуоресцентность после индикации по сочетаниям хлор-бензойных кислот. С использованием этих индикаций деградация PCB может наблюдаться лишь в искусственных условиях и лишь в почве.Ключевые слова: биоиндикаторы, Pseudomonas fluorescens F113, PCBs, ризосфера, корневая колонизация.First Published Online: 14 Oct 2010